Histone H2A: a promising diagnostic marker in heart failure with reduced versus preserved ejection fraction - Tsoneva, Desislava K; Buzova, Diana; Bianco, Salvatore Daniele; Kisheva, Antoniya; Rushid, Mesut; Ivanova, Tanya; Yotov, Yoto; Cerveny, Jan; Mazza, Tommaso; Vinciguerra, Manlio (Molecular and cellular biochemistry, 2025)
The diagnosis of heart failure with preserved left ventricle ejection fraction (HFpEF) remains a challenge, with score-based algorithms showing varying diagnostic performance and biomarkers sometimes inconclusive. This study aimed to examine whether circulating histones and histone complexes, which recently emerged as robust biomarkers of inflammation and stroke, show distinct profiles in plasma from healthy individuals, HF with reduced EF (HFrEF), and HFpEF patients. We evaluated the plasma histone profile of 30 sex/age-matched healthy individuals, 22 HFpEF and 25 HFrEF prior any therapeutic intervention. ImageStreamX-based detection approach was used to measure the levels of circulating particles positive for core histones H2A, H2B, H3, H4, histone variants macroH2A1.1 and macroH2A1.2. While we found increased levels of most of the histones and histone complexes in both HFpEF and HFrEF patients, H2A was significantly elevated only in HFpEF, compared to healthy individuals (p-value = 0.002) and to HFrEF (p-value = 0.00008). In line with these findings, H2A showed positive correlation with EF (r = 0.493). We identified a plasma histone profile able to detect HF and differentiate between HFpEF and HFrEF using a high throughput and imaging flow cytometry-adapted liquid biopsy.
Keywords: tepový objem; Humans; Heart failure; Heart Failure; Stroke Volume; srdeční selhání; lidé středního věku; histony; Female; Aged; Liquid biopsy; senioři; lidé; Biomarkers; Preserved ejection fraction; Reduced ejection fraction; ženské pohlaví; biologické markery; Male; Middle Aged; Plasma; Histones; mužské pohlaví